A Critical Evaluation of the Nonparametric Approach to Estimate Terrestrial Evaporation - Yongmin Yang; Hongbo Su; Jianwei Qi (Advances in Meteorology)
Evapotranspiration (ET) estimation has been one of the most challenging problems in recent decades for hydrometeorologists. In this study, a nonparametric approach to estimate terrestrial evaporation was evaluated using both model simulation and measurements from three sites. Both the model simulation and the in situ evaluation at the Tiger Bush Site revealed that this approach would greatly overestimate ET under dry conditions (evaporative fraction smaller than 0.4). For the evaluation at the Tiger Bush Site, the difference between ET estimates and site observations could be as large as 130 W/m2. However, this approach provided good estimates over the two crop sites. The Nash-Sutcliffe coefficient (E) was 0.9 and 0.94, respectively, for WC06 and Yingke. A further theoretical analysis indicates the nonparametric approach is very close to the equilibrium evaporation equation under wet conditions, and this can explain the good performance of this approach at the two crop sites in this study. The evaluation indicates that this approach needs more careful appraisal and that its application in dry conditions should be avoided.